Results from neoadjuvant chemotherapy followed by surgery compared to chemoradiation for Stage IB2-IIB cervical cancer: EORTC55994. (1st November 2019) - Greggi, S; Kenter, G; Vergote, I; Katsaros, D; Kobierski, J; Massuger, LFAG; van Doorn, PA; Landoni, F; van de Velden, J; Reed, N; Coens, C; van Luijk, I; et al.
Abstract : Introduction/Background: Within EORTC-GCCG we conducted a randomized multinational multicenter trial in order to compare the value of neoadjuvant chemotherapy followed by radical surgery with standard concomitant chemoradiation in Stage IB2-IIB cervical carcinoma. As the trial (55994) is approaching completion of its follow-up, preliminary results are presented here. Methodology: Between May 2002 and June 2014 a total of 620 patients with FIGO stage Ib2-IIb were randomized between neoadjuvant chemotherapy followed by surgery (NACTS, arm1, N=311) with standard concomitant chemoradiotherapy (CCRT, arm2, N=309). In arm1, radical hysterectomy was required within 6 weeks after completion of cisplatin-based chemotherapy with a cumulative minimum of 225 mg/m 2, in arm2, radiation consisted of 45-50Gy plus boost concurrent with weekly cisplatin chemotherapy (40 mg/m 2 per week). Primary endpoint was 5-yr overall survival (OS). Results: Median follow-up time was 8.2 years (95%CI =7.8 yrs–8.6 yrs) and similar between both arms. A total of 191 deaths (31%) occurred. Age, stage and histological cell type were balanced in both arms. Protocol treatment was completed in 459 (74%) patients (71% for NACTS; 82% for CCRT). In arm1 238 (76%) patients underwent surgery. Main reasons for not having surgery as per protocol, were toxicity (25/74, 34%), progressive disease (18/74, 24%) and insufficient response to NACT (12/74, 16%). Additional radiotherapy was given to 113 patients (36.3%) in arm1; additional surgery performed in 9 patients (2.9%) in arm2. Short term severe adverse events (≥G3) occurred more frequently in arm1 than in arm2 (35% vs 21%, p<0.001). The 5 year OS was 72% in arm1 and 76% in arm2 (not statistically significant, difference =4.0% (95%CI: -4%–12%); HR 0.87, 95%CI: 0.65–0.15, p=0.332). Conclusion: These preliminary results revealed no difference in 5-year OS between NACTS and CCRT, indicating that quality of life and long term toxicity across prognostic factors are important to decide on optimal treatment. Disclosure: Nothing to disclose.